DEFINING SOCIAL SUSTAINABILITY AND SOCIALLY CONSCIOUS TOURIST IN SUSTAINABLE TOURISM DEVELOPMENT - Agusta Ika Prihanti Nugraheni; Tri Kuntoro Priyambodo; Bayu Sutikno; Hendrie Adji Kusworo (Institut Pariwisata dan Bisnis Internasional, 2019)
Sustainable Tourism Development (STD) consists of three dimensions known as environment, economic and social. Although these three dimensions influence each other and cannot stand on their own, and are assumed to be supportive to each other and compatible. However, most studies focus on the environmental and economic dimensions. The social dimension gains less attention and is difficult to attain and operationalize. In order to implement a balanced and successful STD, it needs to be supported by all the tourism stakeholder, including the tourist itself. Therefore, it is necessary to explore the social dimension of STDs and also tourist behavior regarding their social conscious. However, the discussions and understanding of social dimension in STD and socially conscious behavior are still limited. This study aims to define a clear understanding and definition of social dimension of STD which in this study is referred as social sustainability and also a socially conscious tourist. Starting with exploring the aspect of social dimensions formulation and exploring clear definitions of social dimensions of STD's and socially conscious tourist. This study is an exploratory study that aims to explore the boundaries of social dimension of STD and to develop a construct of socially responsible tourist. This study is a qualitative approaches, which includes systematic literature review and Delphi method to obtain expert judgment to gather social dimension aspects of sustainable development, especially in STD. The results of this study are social dimension’s aspects of STD, an understanding of social sustainability and socially conscious tourist in STD.